Mobile learning in science education to improve higher-order thinking skills and communication skills: scoping review - Galimova, Elvira G.; Sergeeva, Olga V.; Zheltukhina, Marina R.; Sokolova, Natalia L.; Zakharova, Valeria L.; Drobysheva, Nataliya N. (Frontiers in Communication, 2025)
Mobile devices increasingly permeate students’ lives, yet their impact on core 21st-century competencies in science classrooms remains unevenly charted. This scoping review maps how mobile-learning interventions influence higher-order thinking skills (HOTS) and communication skills across primary, secondary and tertiary science education. Guided by Arksey and O’Malley’s five-stage framework and reported in line with PRISMA-ScR, six databases were searched for English-language studies published between 1 January 2015 and 31 March 2025. Twenty-seven empirical papers met the inclusion criteria and were charted for context, pedagogy, technology and outcomes. Most interventions originated in Indonesia and combined purpose-built science apps or smartphone sensors with ubiquitous chat platforms such as WhatsApp or Viber. Inquiry and problem-based models dominated, typically embedding real-time data collection, instant peer sharing and scaffolded reflection. Across studies, moderate-to-large gains were reported for critical thinking, creativity and, to a lesser extent, verbal and written scientific communication. Designs that coupled evidence gathering with public dissemination (e.g., WeChat science posts) yielded the strongest communication improvements. Recurring challenges included short intervention windows, small intact-class samples, technical glitches and limited teacher preparation. The review concludes that mobile devices can catalyze sustained HOTS and richer scientific discourse when inquiry-rich tasks are buttressed by social-communication channels and graduated scaffolds. Future research should extend trials over full semesters, diversify geographic settings and employ process analytics to trace how mobile interactions translate into durable learning.